Dot1l Regulates the Spontaneous Bone Regeneration of Periosteum-Derived Stem Cells by Regulating Chac1 Expression - Taoran Jiang; Bin Fang; Zheyuan Yu; Dejun Cao (Stem Cells International, 2025)
Conclusions: Our study suggests that mandibular defects can induce the activation of PDSCs and inhibit the expression of Dot1l, potentially affecting the Notch signaling pathway. Targeting the Dot1l/Chac1 pathway to regulate the osteogenic differentiation of PDSCs lays a solid foundation for periosteum-based maxillofacial bone regeneration.